KHITANAN MASSAL DI MASA PANDEMI VIRUS CORONA DENGAN SMARTCLAMP - Supartono, Basuki -; Ibnu Khaldun, Muhammad; Tounso Abdennour, Aronica -; Maulana, Rayhan; Mahasin, Dhial Falah (Jurnal Bakti Masyarakat Indonesia, 2021)
Coronavirus pandemic (pandemic) decreases the economic capabilities of the communities while they want to circumcise their children. There is a need for free mass circumcision activities. Mass circumcision in pandemics is risky but can be done by implementing smart clamp health protocols, screening, and circumcision techniques. There is a need for the Kramat Jati sub-district, East Jakarta, to circumcise their children. People are afraid to go to health facilities because of coronavirus transmission, and the circumcision is paid. People's economic capabilities are declining due to pandemics. There need to be community service activities that are free mass circumcision that is safe and convenient. Pandemics cause people difficulties in circumcising their children. Free mass circumcision is safe and convenient with implementing health protocols, screening, and smart clamp circumcision techniques. Mass circumcision was successfully carried out safely and comfortably in 55 participants, with the youngest age two years and the oldest 12 years. The majority of participants were seven years old. Found mild complications of swelling in 4 children. Symptoms that occur subside within a week. Participants and parents were satisfied. After mass circumcision, there were no participants, parents, health workers, or organizers infected with the coronavirus. Free mass circumcision in pandemic times was successfully implemented safely and comfortably ABSTRAK Pandemi virus corona (pandemi) menurunkan kemampuan ekonomi masyarakat sedangkan masyarakat ingin mengkhitan anaknya. Hal inilah mendorong diadakannya kegiatan khitanan masal gratis. Khitanan massal di masa pandemi berisiko namun dapat dilakukan dengan menerapkan protokol kesehatan, skrining, dan teknik khitan yang cepat menggunakan smartclamp. Terdapat kebutuhan masyarakat kecamatan Kramat Jati, Jakarta Timur untuk mengkhitan anaknya. Masyarakat takut ke fasilitas kesehatan karena kawatir penularan virus corona dan tindakan tersebut berbayar. Kemampuan ekonomi masyarakat menurun akibat pandemi. Perlu ada kegiatan pengabdian masyarakat yaitu khitanan massal gratis yang aman dan nyaman. Pandemi menyebabkan kesulitan masyarakat mengkhitan anaknya. Khitanan massal gratis yang aman dan nyaman dengan penerapan protokol kesehatan, skrining dan teknik khitan smartclamp. Khitanan massal berhasil dilakukan secara aman dan nyaman pada 55 peserta dengan usia termuda 2 tahun dan tertua 12 tahun. Peserta terbanyak berusia 7 tahun. Terdapat komplikasi ringan yaitu bengkak pada 4 anak. Gejala mereda dalam waktu satu pekan. Peserta dan orangtua merasa puas. Pasca khitanan massal tidak ada peserta, orangtua, tenaga kesehatandan panitia yang terinfeksi virus corona. Khitanan massal gratis di masa pandemi berhasil dilaksanakan secara aman, dan nyaman.